2019
DOI: 10.1007/s00162-019-00499-7
|View full text |Cite
|
Sign up to set email alerts
|

Layer formation in double-diffusive convection over resting and moving heated plates

Abstract: We present a numerical study of double-diffusive convection characterized by a stratification unstable to thermal convection while at the same time a mean molecular weight (or solute concentration) difference between top and bottom counteracts this instability. Convective zones can form in this case either by the stratification being locally unstable to the combined action of both temperature and solute gradients or by another process, the oscillatory double-diffusive convective instability, which is triggered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Therefore, understanding the dynamical properties of how such diffusive DDC staircases can form, and (at least equally importantly) remain robust is a topic of not only fluid dynamical interest but also great climatological importance, and so we focus on such staircases here. Diffusive staircases have been observed to develop spontaneously, even in numerical simulations restricted to two dimensions both with and without shear (Noguchi & Niino 2010; Zaussinger & Kupka 2018), but their actual formation mechanism has up to now remained somewhat mysterious, as discussed by Kelley et al. (2003) and Turner (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the dynamical properties of how such diffusive DDC staircases can form, and (at least equally importantly) remain robust is a topic of not only fluid dynamical interest but also great climatological importance, and so we focus on such staircases here. Diffusive staircases have been observed to develop spontaneously, even in numerical simulations restricted to two dimensions both with and without shear (Noguchi & Niino 2010; Zaussinger & Kupka 2018), but their actual formation mechanism has up to now remained somewhat mysterious, as discussed by Kelley et al. (2003) and Turner (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biello [26] found that gravity waves can break near the interface and mix the composition gradient across, making the formation of secondary layers difficult to occur at low Pr. On the other hand, Zaussinger and Kupka [27] found that multiple layers can form at low Pr either by a thermal instability at the interface ahead of the main convective layer, or spontaneously develop due to double-diffusive instabilities, as the ones observed in Radko [14] and Mirouh et al [16]. We will discuss these issues in a companion paper.…”
Section: Equations (mentioning
confidence: 87%
“…5 Eq. (27) shows that the range of values of R ρ depends on the maximum value of γ. The definition of γ in eq.…”
Section: Analytic Model For the Inwards Propagation Of The Convective...mentioning
confidence: 95%
See 2 more Smart Citations